2015
DOI: 10.1128/aac.05006-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epidemic IncI1-Iγ Plasmids Harboring Ambler Class A and C Genes in Escherichia coli and Salmonella enterica from Animals and Humans

Abstract: The aim of the study was to identify the plasmid-encoded factors contributing to the emergence and spread of epidemic IncI1-I␥ plasmids obtained from Escherichia coli and Salmonella enterica isolates from animal and human reservoirs. For this, 251 IncI1-I␥ plasmids carrying various extended-spectrum ␤-lactamase (ESBL) or AmpC ␤-lactamase genes were compared using plasmid multilocus sequence typing (pMLST). Thirty-two of these plasmids belonging to different pMLST types were sequenced using Roche 454 and Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 52 publications
11
48
1
Order By: Relevance
“…Our data revealed that resistance to ceftriaxone in S. Enteritidis is mainly due to the transmission of various IncI1 conjugative plasmids carrying various bla CTX-M genes. Our data corroborate the results of recent studies that these types of plasmids have the potential to be spread in Salmonella and other bacterial species (15,16). Future studies should focus on monitoring the transmission routes and assessing …”
supporting
confidence: 90%
“…Our data revealed that resistance to ceftriaxone in S. Enteritidis is mainly due to the transmission of various IncI1 conjugative plasmids carrying various bla CTX-M genes. Our data corroborate the results of recent studies that these types of plasmids have the potential to be spread in Salmonella and other bacterial species (15,16). Future studies should focus on monitoring the transmission routes and assessing …”
supporting
confidence: 90%
“…For instance, ST7, ST31, ST37 plasmids show the traY-excA genes of R621a but the inc sequences are 100% identical to that of R64. ST7 has the parAB genes of R64; ST37 has the parAB of R621a; and ST31, instead of parAB genes, has the soj-yfhA genes, previously described as a partitioning system (Smith et al, 2015) (Smet et al, 2010).…”
Section: Inci1 and Inciγ Plasmid Evolutionmentioning
confidence: 99%
“…In recent years, plasmids of the IncI1 and IncIγ families have been recognized in clinically relevant bacteria from human, animal and environmental sources (Carattoli, 2009) (Carattoli, 2011). Comparative analysis of fully sequenced plasmids has shown that contemporary IncI1 and IncIγ plasmids have structures consistent with those of historical reference plasmids, including conserved replication, stability, leading and transfer regions (Takahashi et al, 2011) (Smith et al, 2015) (Johnson et al, 2011). Beyond the conserved backbone, most IncI1 and IncIγ plasmids also contain variable regions such as AMR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of E coli and Salmonella enterica from the same national collections as used in the study by Wu and others examined epidemic IncI1-Iγ plasmids and found similar plasmid-gene combinations from different animal sources and from humans, which the authors said ‘suggests transmission between animal and human isolates, as was previously assumed’ (Smith and others 2015). Similarly, research in the Netherlands using whole-genome sequencing methods found that genetically unrelated human and animal E coli carried nearly identical plasmids (IncI1- and IncK- types) conferring cephalosporin resistance (de Been and others 2014).…”
mentioning
confidence: 80%